2021
DOI: 10.1039/d1sc03701c
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning to tame divergent density functional approximations: a new path to consensus materials design principles

Abstract: Virtual high-throughput screening (VHTS) with density functional theory (DFT) and machine-learning (ML)-acceleration is essential in rapid materials discovery. By necessity, efficient DFT-based workflows are carried out with a single density...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(70 citation statements)
references
References 129 publications
(264 reference statements)
5
65
0
Order By: Relevance
“…25 Although benchmarking studies [26][27][28] can be used to identify the best density functional approximation (DFA) to yield accurate energetic properties for a chosen class of material, the choice of DFA depends strongly on the system of interest and cannot be determined a priori in VHTS where most materials have yet to be characterized. 29,30 Moreover, an imbalanced treatment of systems that have weak or strong MR character can be expected to undermine the data delity and bias the candidate materials recommended by chemical discovery efforts. 31 To quantify the degree of MR character, researchers have devised many MR diagnostics 24,[32][33][34][35][36][37][38][39][40][41][42] based on different properties (e.g., occupations or atomization energies) and levels of theory.…”
Section: Introductionmentioning
confidence: 99%
“…25 Although benchmarking studies [26][27][28] can be used to identify the best density functional approximation (DFA) to yield accurate energetic properties for a chosen class of material, the choice of DFA depends strongly on the system of interest and cannot be determined a priori in VHTS where most materials have yet to be characterized. 29,30 Moreover, an imbalanced treatment of systems that have weak or strong MR character can be expected to undermine the data delity and bias the candidate materials recommended by chemical discovery efforts. 31 To quantify the degree of MR character, researchers have devised many MR diagnostics 24,[32][33][34][35][36][37][38][39][40][41][42] based on different properties (e.g., occupations or atomization energies) and levels of theory.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting approach to solving this process looks at using computational models to help design/monitor the design workflow by scoring the “safety” of calculation methods (based on DFT). 180 Automated approaches, like ours in stk , 95,99 and those of the Duarte, 101,143 and Hay groups 80 show progress in developing generalisable design workflows to explore MOCs. Overall, the development of low-cost cheminformatic, semiempirical and DFT approaches using large and diverse benchmark sets can provide robust and broadly applicable methods for studying MOCs with reasonable accuracy, which is crucial for high-throughput design processes.…”
Section: Discussionmentioning
confidence: 93%
“…Although transition metals in chemical systems often have multiconfigurational character [120], there have been several DFT studies [121][122][123] reported that utilized the M06-2X functional [42] for applications involving main-group thermochemistry, kinetics, noncovalent interactions, and electronic excitation energies to valence and Rydberg states. Wang et al have demonstrated that the M06 and M06-2X hybrid metafunctionals have broad applicability, including transition metal systems [122].…”
Section: Computational Methodologymentioning
confidence: 99%